The influence of a visual target point on the onset of visual regulation and kinematics on the approach run while performing the Tsukahara vault in artistic gymnastics - Karagiota, Emmanouela; Dallas, Costas; Dallas, George; Smirniotou, Athanasia; Theodorou, Apostolos (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. The study examined if a visual target for the hurdle take-off affects the onset of visual regulation and hurdle kinematics during the approach run in a vaulting event.Methods. Ten high-level male artistic gymnasts (23.9 ± 4.2 years; body mass = 63.7 ± 6.4 kg; body height = 168.00 ± 0.11 cm) performed the Tsukahara vault using a visual target marking the last touchdown of the approach run and the com-mencement of the hurdle (tape condition) and under standard vaulting regulations (non-tape condition). Gymnast’s trials were performed under training conditions, with five high-speed cameras (four stationary and one panning) used for the collection of the spatiotemporal characteristics of the approach run and hurdle.Results. Although a faster onset of visual regulation was revealed in the tape condition, no statistically significant differ-ences were found between the two conditions in the kinematic characteristics of athletes’ run-ups. Furthermore, the profile of the average standard deviation for the contact positions of gymnasts’ feet/soles differed in the two examined conditions.Conclusions. The presence of a visual target positively affected the onset of visual regulation when high-level artistic gym-nasts performed the Tsukahara vault.
Keywords: perception; approach run; vault; artistic gymnastics; visual regulation